Characterization of the structure–function relationship at the ligament-to-bone interface - Moffat, Kristen L. (National Academy of Sciences, 2008)
Soft tissues such as ligaments and tendons integrate with bone through a fibrocartilaginous interface divided into noncalcified and calcified regions. This junction between distinct tissue types is frequently injured and not reestablished after surgical repair. Its regeneration is also limited by a lack of understanding of the structure–function relationship inherent at this complex interface. Therefore, focusing on the insertion site between the anterior cruciate ligament (ACL) and bone, the objectives of this study are: (i) to determine interface compressive mechanical properties, (ii) to characterize interface mineral presence and distribution, and (iii) to evaluate insertion site-dependent changes in mechanical properties and matrix mineral content. Interface mechanical properties were determined by coupling microcompression with optimized digital image correlation analysis, whereas mineral presence and distribution were characterized by energy dispersive x-ray analysis and backscattered scanning electron microscopy. Both region- and insertion-dependent changes in mechanical properties were found, with the calcified interface region exhibiting significantly greater compressive mechanical properties than the noncalcified region. Mineral presence was only detectable within the calcified interface and bone regions, and its distribution corresponds to region-dependent mechanical inhomogeneity. Additionally, the compressive mechanical properties of the tibial insertion were greater than those of the femoral. The interface structure–function relationship elucidated in this study provides critical insight for interface regeneration and the formation of complex tissue systems.